Comments on Watson’s "Empirical Analysis of the Hugh Gray ’Nessie’ Photograph" - Champagne, Bruce (Journal of Scientific Exploration, 2023)
I would like to comment on Watson’s interesting paper in the Spring 2022 Journal of Scientific Exploration on the subject of the 1933 Hugh Gray Loch Ness photograph. Having a couple of Roland Watson’s books in my personal library (which I strongly recommend) and having corresponded with him for his opinion and thoughts in my own research, I can assure the reader that Watson has a significant knowledge of the history and current thought on the subject of the Loch Ness Monster (LNM) and other unidentified aquatic megafauna of the area. I would suggest this paper would benefit, and the proposals strengthened, with a greater and more consistent application and methodology (Heuvelmans, 1988) and a greater effort towards explanations of any imbalance.